Cotargeting of Mitochondrial Complex I and Bcl-2 Shows Antileukemic Activity against Acute Myeloid Leukemia Cells Reliant on Oxidative Phosphorylation - Fangbing Liu; Hasini A. Kalpage; Deying Wang; Holly Edwards; Maik Hüttemann; Jun Ma; Yongwei Su; Jenna L. Carter; Xinyu Li; Lisa Polin; Juiwanna Kushner; Sijana H. Dzinic; et al. (2020)
Targeting oxidative phosphorylation (OXPHOS) is a promising strategy to improve treatment outcomes of acute myeloid leukemia (AML) patients. IACS-010759 is a mitochondrial complex I inhibitor that has demonstrated preclinical antileukemic activity and is being tested in Phase I clinical trials. However, complex I deficiency has been reported to inhibit apoptotic cell death through prevention of cytochrome c release. Thus, combining IACS-010759 with a BH3 mimetic may overcome this mechanism of resistance leading to synergistic antileukemic activity against AML. In this study, we show that IACS-010759 and venetoclax synergistically induce apoptosis in OXPHOS-reliant AML cell lines and primary patient samples and cooperatively target leukemia progenitor cells. In a relatively OXPHOS-reliant AML cell line derived xenograft mouse model, IACS-010759 treatment significantly prolonged survival, which was further enhanced by treatment with IACS-010759 in combination with venetoclax. Consistent with our hypothesis, IACS-010759 treatment indeed retained cytochrome c in mitochondria, which was completely abolished by venetoclax, resulting in Bak/Bax- and caspase-dependent apoptosis. Our preclinical data provide a rationale for further development of the combination of IACS-010759 and venetoclax for the treatment of patients with AML.